A painted geography: landscape and abstract art in fictions and essays of Juan José Saer (Anclajes, 2017)
Juan José Saer’s literature and essays, as well as most of the criticism about the author, allow for exploration of the idea of “zone” expressed in diverse forms throughout his career. This paper attempts to revisit some of these considerations and address the pictorial aspect of his works. The various avant-garde movements that began to emerge between the late fifties and early sixties helped shape a new image of the Argentine littoral region. Saer, who often met with avant-gardists in the cities of Santa Fe and Rosario, joined in these literary and visual renewal movements and incorporated into his literature forms, materials, and manners of observation that resulted from these various abstract tendencies, mainly abstract expressionism and geometric abstraction. The aim here is to observe how Saer “disrealizes” the traditional landscape based on these figures and thus challenges the hasty relationship that early critics established between his texts and a more or less traditional realism.
Keywords: Juan José Saer; Argentine literature; visual arts; 20th century; Argentina